Воздух Таврики - Глазунова, С.А. (Культура народов Причерноморья, 2013)
Статья посвящена творчеству Заслуженного художника Украины и Автономной
Республики Крым Николая Яковлевича Дудченко. Автор делает краткий обзор ряда направлений
творчества художника в период 1980 - 2000-х годов. Особое внимание в статье уделено воплощению
образов украинской национальной культуры в творчестве Николая Дудченко. В статью включен
авторский комментарий содержательной, образной и пластической структуры двенадцати
произведений художника, а также краткие биографические сведения о нем. Стаття присвячена творчості Заслуженого художника України і Автономної Республіки
Крим Миколая Яковича Дудченко. Автор робить стислий огляд ряду напрямів творчості художника у
період 1980 – 2000-х років. Особлива увага у статті приділяється втіленню образів української
національної культури в творчості Миколая Дудченко. До статті включено авторські коментарі
змістовної, образної та пластичної структури дванадцяти творів художника, а також стислі
біографічні відомості про нього. The article «The Atmosphere of Tavrika» is devoted to the work of Niсolay Dudchenko - the Honored
Artist of Ukraine and the Autonomous Republic of the Crimea. The author makes a short overview of some
directions of the artist's work in the period of 1980 - 2000's. A special attention in the works of Nicolay
Dudchenko is paid to the incarnation of the image of the national culture. This article includes the author's
comment of informative, imaginative and plastic structure of the twelve works of the artist, as well as brief
biographical information about him.
The author of article emphasizes the "Rural iconostasis" as one of the most picturesque cycles of artist. The
theme of this cycle passes through all the work of Nicholas Dudchenko. Artist invests reflection about eternity in
the figurative–symbolic formulas. Color, texture, the maximum restraint and terseness of the composite solutions
are the guarantee of our immersion in an atmosphere of prayerful Deisis.
The creation of Nicholas Dudchenko exposes deep existential problems and is read as a reflection of the
spiritual portrait of a people or a whole region. Meeting with his works emotionally enriching the understanding
of the spirit of southern Ukraine and Tavrika, judicial and poetic life of this land.